2016
DOI: 10.4168/aair.2016.8.4.312
|View full text |Cite
|
Sign up to set email alerts
|

No Concentration Decrease of House Dust Mite Allergens With Rising Altitude in Alpine Regions

Abstract: PurposeSeveral studies over the past 4 decades have indicated a significant reduction in house dust mite (HDM) and HDM allergen concentration in areas higher than 1,500 m above sea level. These have served as basis of allergen avoidance therapies for HDM allergy and asthma. However, modern construction techniques used in the insulation, heating, and glazing of buildings as well as global warming have changed the environmental parameters for HDM living conditions. The present study revisits the paradigm of decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
2
14
1
Order By: Relevance
“…These findings correlate well with other studies showing decreased exposure in high altitudes [42, 43], and lower sensitization prevalence in alpine or dry regions [44, 45]. Interestingly, a recent study did not find a correlation between altitude and mite allergens in alpine regions of Germany and Austria but also noted lower Der f 1 levels at elevated altitudes [24]. Divergent outcomes may be due to investigations of homes as well as taverns and mountain huts in the latter study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings correlate well with other studies showing decreased exposure in high altitudes [42, 43], and lower sensitization prevalence in alpine or dry regions [44, 45]. Interestingly, a recent study did not find a correlation between altitude and mite allergens in alpine regions of Germany and Austria but also noted lower Der f 1 levels at elevated altitudes [24]. Divergent outcomes may be due to investigations of homes as well as taverns and mountain huts in the latter study.…”
Section: Discussionsupporting
confidence: 91%
“…Also, exposure itself is influenced by different factors such as pet ownership, infrastructural characteristics or altitude. These influences are widely discussed in the literature and strong differences in exposure between groups [6, 2123] as well as no effects [24] from specific influencing factors are found. In order to assess allergen exposure, it is well established to measure allergen concentrations in house dust samples using antibody-based detection systems [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this cohort of children from 6 to 15 years old with SA residents at HA (2640 meters) in a tropical middle‐income developing country, we found a very high frequency of HDM sensitization (87.9%) and atopic phenotype, defined as at least one positive SPT (88.7% in our study), and high levels of IgE and FE NO . Differently from previous studies in Europe that have shown a low rate of HDM sensitization at HA, our study ratifies observations from other tropical country (Ecuador) and in other more recent European study that have shown high HDM sensitization at HA.…”
Section: Discussionsupporting
confidence: 85%
“…[14] HDM concentrations at sea level and at HA did not differ significantly in one study performed at altitudes from 400 to 2600 meters in the Alps. [8] More than half of all dust samples (53.3%) were collected at altitudes below 1500 m. [8] Another study performed at over 1500 m in the Alps found that positive HDM skin test results were significantly fewer in mountain schoolchildren, and the levels of HDM antigens in mattresses were much lower than those at sea level. [7] One study evaluated the prevalence of allergic diseases (rhinoconjunctivitis and asthma) in 3196 children living 3658 m above sea level in Lhasa, Tibet.…”
Section: Degree Of Altitudementioning
confidence: 99%
“…[6,7] However, some studies found that HA did not benefit those with allergic respiratory disease. [8][9][10] We sought associations among HA, allergic rhinitis, and bronchial hyperreactivity in which relevant literature was reviewed.…”
mentioning
confidence: 99%